Analisis Manajemen Proyek Pembangunan Mako Polsek Gemolong dan Fasum terhadap Kinerja Mutu, Biaya dan Waktu TA 2024 - Yudi Suzandi; Antonius Antonius; Kartono Wibowo (Portal: Jurnal Teknik Sipil, 2025)
The construction of the Gemolong Police Sector Headquarters (Mako Polsek Gemolong) and public facilities in Sragen is a state-owned project built from June 4, 2024, to October 31, 2024. This facility serves as a center for public services and complaints to the Indonesian National Police. The construction includes four detention rooms, each with a maximum capacity of five detainees. These detention rooms are not intended for permanent detention but as temporary holding cells before transfer to permanent prisons. This study assesses the effectiveness of implementing quality, cost, and time management during the construction process. The analytical method used involves comparing the implementation of quality management with the Technical Specifications, comparing the Project Implementation Budget Plan (RAP) with the contractual Budget Plan (RAB), and comparing the initial work schedule (Time Schedule) with the actual field implementation. The findings show that quality management during the construction of the Gemolong Police Headquarters and public facilities met the required technical specifications. However, cost management was deemed unsuccessful because the implementation cost reached IDR 3,625,017,095.07, exceeding the contractual value of IDR 3,414,445,000.00, resulting in the failure to achieve the expected 10% profit margin. Time management was also considered unsuccessful due to a 30-working-day delay in project completion. Based on these results, it is recommended that the Commitment-Making Officer (PPK) review the application of contractual provisions in construction projects and that relevant stakeholders pay greater attention to the implementation of quality, cost, and time management principles in future projects.